Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Judge James V. Paige in costume at microphone by Judge Sandra Snyder playing Princess Laya; Harold Lai in costume in background 5080 E. Kings Canyon Road, Fresno